Atherosclerosis prevalence and the correlation between atherosclerosis risk factors and carotid intima-media thickness in below 40-year-old women with systemic lupus erythematosus - R M Sari; Yoga I Kasjmir; D Antono; S Setiati (Indonesian Journal of Rheumatology, 2010)
Objectives: To determine the prevalence of atherosclerosis in female systemic lupus erythematosus (SLE) patients aged below 40 years old and the factors correlated with carotid intima-media (CIM) thickening.Methods: A cross-sectional study was conducted on 80 female SLE respondents aged below 40 years old who were either in- or outpatient of Cipto Mangunkusumo General Hospital, Jakarta. History of disease and treatment was taken, and laboratory test andÂ  ultrasonography of the carotid artery to evaluate CIM thickness were performed.Results: The prevalence of atherosclerosis was 40%, comprising of CIM thickening and/or presence of atherosclerotic plaque in the carotid artery. The median values of CIM thickness in the right common carotid artery, right carotid bulb, left common carotid artery, and left carotid bulb were 0.040 cm, 0.04535 cm, 0.0430 cm, and 0.047 cm, respectively. There was also a positive correlation reported of CIM thickness with increased age, the duration of SLE disease, and the duration of steroid treatment.Conclusions: We found a positive correlation of CIM thickness with age, the duration of SLE disease, and the duration of steroid treatment in female SLE patients aged below 40 years.